Performance analysis of effective microorganisms on chicken manure composting - Gunawan, Velisia Chandra; Shamsuddin, Muhammad Rashid bin; Mat Isa, Noor Hanani bin; Julaihi, Muhammad Rafiq Mirza bin (Science, Engineering and Health Studies, 2020)
Effective microorganisms (EM) in organic waste management converts poultry manure into high-quality biofertilizer. However, the production of biofertilizer is limited by the high price of imported EMs that are currently used in the poultry industry. Untreated manure will attract flies that will cause environmental problems. Therefore, it is necessary to find effective, locally available, and affordable alternatives to the current imported EMs. This study aimed to determine suitable local EMs based on cost and compost quality. Specifically, in terms of nitrogen (N), phosphorus (P), potassium (K), sodium (Na) and magnesium (Mg) composition. Five batches of chicken manure were prepared with two control setups of manure only and manure with sawdust (at carbon to nitrogen ratio, C/N of 30:1). The remaining batches of manure treated with different commercial EMs. Temperature and pH values were measured every 3 days for 45 days. The highest temperature recorded was 45ºC and the measure pH was between 4.0 to 6.5. Composts matured after 24, 27 and 45 days for EM1 (local), EM3 (imported) and EM2 (local), respectively. The highest values obtained for K (412 ppm), Na (233 ppm) and Mg (54 ppm) with low energy (11.7 kJ/g) and application cost (RM 171/tonne manure) suggest that EM3 was the best option. However, the higher NPK values of EM2 and faster maturation of EM1 also make them promising local substitutes. Future work should investigate the potential mixture of these EMs for optimum composting time and quality.